Are neural pathways processing airway inputs sensitized in patients with cough hypersensitivity?. (August 2019) - Farrell, Michael J.; Mazzone, Stuart B.
Abstract: Patients with cough hypersensitivity exhibit unusually low thresholds for responses to tussive stimuli, exaggerated responses to suprathreshold tussive stimuli, and report spontaneous experiences of urge-to-cough in the absence of exogenous stimulation. These aberrant responses to tussive challenge have the hallmark features of behaviours associated with a sensitized sensory system. Searching for further evidence to implicate neural sensitization in the symptomatology of cough hypersensitivity warrants consideration. If up-regulation of neural circuits involved in processing of airways inputs can be demonstrated in patients with cough hypersensitivity, then strategies to reverse this dysfunctional plasticity can be contemplated and assessed. This review considers the implications of neural sensitization as a factor in the cough hypersensitivity syndrome, reflects on the limited data available in this field, and suggests prospective directions for future research.